EFFECT OF SUPPLEMENTED MUAY THAI CIRCUIT TRAINING PROGRAM ON MAXIMAL OXIGEN UPTAKE AND PHYSICAL PERFORMANCE IN PROFESSIONAL MUAY THAI BOXERS - Nukeaw, Aritach; Boonrod, Wanchai (Journal of Sports Science and Health, 2020)
Purpose : This research aimed to determine the effects of supplemented Muay Thai circuit training program on maximal oxygen uptake and physical performance in professional Muay Thai boxer. Methods : Fifteen professional Muay Thai boxers, aged between 19-22 years old, volunteered for this study. They were divided into two groups; an experimental group (n=8) and a control group (n=7). The experimental group was trained by Muay Thai circuit training program in addition to their regular training, 3 days a week for 6 weeks, whereas the control group, underwent a regular training program only. Maximal oxygen uptake (VO2max) was measured by using a Bruce protocol and physical performance was tested using a simulation match of Muay Thai. Data were presented as mean and standard deviation, and were analyzed using Pair t-test and Independent sample-t test. A level of significant was set at p-value < 0.05. Results : The results showed that after 6-week of training the experimental group had a greater improvements in VO2max and recovery heart rate during a simulation match of Muay Thai compared to pre training (p<0.05). In addition, the number of attack in the experimental group was higher than that of control group and pre training (p<0.05). Conclusion : The Muay Thai circuit training program employed in the present study is effective and sport specific exercise program for improving maximal oxygen uptake and physical performance of professional Muay Thai boxer.